Theoretical bases of domestic and foreign practice history of SOS Children's village formation - Akhmetov, R.A.; Baymukanova, M.T.; Kozyrskaya, I. (KSU publ., 2020)
The authors argue within the framework of the SOS Children's village to provide a worthy child psychopedagogical assistance aimed at comprehensive development of the child, develop an individual development plan for each child, according to the plan, provide social support to the child. This article reveals the purpose of the individual development plan-to provide possible assistance in the daily life of the child, the development of his abilities through structured and purposeful pedagogical work. According to the authors, the child also participates in the preparation of an individual development plan and depends on the age of his involvement in this process and the level of his readiness. In this article, it is determined that SOS Children's village works not only with children and adolescents, but also with different types of family. Despite the very sad events in childhood, orphans and social orphans live in SOS Children's villages and SOS youth homes, recover from emotional stress, adapt to society and start a normal independent life. Thus, according to the authors, compared to graduates of orphanages, they are able to live in society, receive education, work and Express themselves, protect their rights, make reasonable decisions, create their own families and take care of them.
Keywords: SOS Children's village; orphanhood; adolescent; psychological and pedagogical assistance; support; development; emotional stability